An Exploratory Study of Telomere Length in the Deep-Sea Shark, Etmopterus granulosus - Nehmens, Melissa C.; Varney, Rebecca M.; Janosik, Alexis M.; Ebert, David A. (Frontiers in Marine Science, 2021)
The history of elasmobranch ageing highlights the difficulty of age estimation in animals lacking ossified structures. Ageing techniques are numerous, yet all are limited by difficulties of validation and verification and inherent subjectivity. Sample scarcity further hinders progress as limited samples cannot be risked on exploratory techniques. This study explored the use of genetic analysis of telomeres as a method of age determination in a deep-sea shark, Etmopterus granulosus, a representative of a poorly studied taxon with regard to ageing due to sample scarcity. Telomeres were amplified in 39 individuals with qPCR, compared across samples, and were found to differ across size classes. More work is needed to determine whether telomeres consistently correlate with size class across elasmobranchs. However, telomeres offer easily obtainable data that can be combined with traditional methods to provide additional points of comparison for elasmobranch biology. Our results underscore the importance of expanding current ageing methods and highlight a necessary distinction between chronological and biological ages when describing elasmobranch populations.